Community Satisfaction Index at PLN Bintuhan, South Kaur District, Kaur Regency (Implementation of the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia No: 14 Tahun 2017) - Suharni Yati; Sulisti Afriani; Nia Indiasari (Journal of Indonesian Management, 2021)
The purpose of this study is to determine the community satisfaction index at PLN Bintuhan in South Kaur Subdistrict of Kaur Regency based on the implementation of The Utilization of the State Apparatus and Bureaucratic Reform of the Republic of Indonesia Regulation Number 14 of 2017. The analysis method used was the Community Satisfaction Survey (SKM) based on The Utilization of the State Apparatus and Bureaucratic Reform of the Republic of Indonesia Regulation Number 14 of 2017 with nine indicators; namely requirements, procedures, completion time, cost, product type service specifications, implementing competencies, implementing behavior, handling complaints of suggestions and input, facilities and infrastructure. From the analysis of the community satisfaction index, 78 with service quality B with good criteria because it is in the range of conversion interval values 76.61 - 88.30. The implementing competency element is the element that gets the highest average score of 3.29 Good criteria. The lowest satisfaction value is the completion time with an average value of 2.78 with a less good rating because it lies at an interval value of 2.60 - 3.064..